If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 6x + -9 Reorder the terms: 6x = -9 + 6x Add '-6x' to each side of the equation. 6x + -6x = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 0 = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 0 = -9 + 0 0 = -9 Solving 0 = -9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3(m+3)-16= | | 36=13w-4w | | X+2=289 | | 10x=-4x+-7 | | -mn+7mp+10m=-2n-8 | | 3a^2+9a+30=0 | | 32=7k-3 | | 4n-6=2n-2n+2 | | X^2-10x-263=0 | | -(1+b)=-(3b-3) | | 2(9-4)+15=13 | | 2(50+-1.5y)+3y=100 | | 52-(2c+3)=4(3+7)+c | | 2(4-5x)=-15x+10 | | s^3-3s^2=5 | | -12p=240 | | 4(3v+7)= | | -100+4*90= | | 71-3x=51 | | 5x-3=2x+8+1 | | 2x+75=4x+91 | | 10z+8m-5z-2= | | -1=2x^2+2x^2+2 | | 7x+14=2x+2 | | -38v-114=-41v-321 | | x+1/2+x+2/3+x+3/4=16 | | 29=8y+(-3) | | t=3s+18.95 | | 13=6+1 | | -1=x^2-5x+2 | | 5x+(-9)=26 | | 1=24-5b |